Information Perception and Participation in Corporate Social Responsibility (CSR) of Employees at Siam Commercial Bank Public Company Limited - วงศ์ทอง เพ็ญประภา; บิลมาโนชญ์ ศศิพรรณ (Siam Communication Review, 2016)
In this thesis, the researcher examines (1) information perception of employees at Siam Commercial Bank Public Company Limited (SCB) in respect to corporate social responsibility (CSR). The researcher also investigates (2) the participation of SCB headquarters employees in CSR. Furthermore, the researcher compares (3) the participation of these employees as classified by demographical characteristics. Finally, the researcher studies (4) the relationships between information perception of CSR projects and the participation of the employees. Applying the Taro Yamané formula, the researcher collected a sample population of 375 SCB employees from a total research population of 6,020 employees. Using techniques of descriptive statistics, the researcher analyzed the data collected in terms of frequency, percentage, mean and standard deviation. Furthermore, the researcher also employed a t-test technique and an analysis of variance (ANOVA) technique, as well as Pearson’s product moment correlation coefficient method. Findings are as follows: 1. In respect to the information perception of CSR by these SCB employees, the following was found: The majority of the sample population exhibited overall information perception at the highest level in all of the three aspects considered. In descending order were network building and volunteering; quality of life development and the environment; and youth development and learning enhancement. 2. Concerning the participation of these employees in CSR projects, the following was found: The majority of the sample population exhibited participation in the operation and in decision making at the highest level (means being 4.26 and 4.25). The participation was at a high level in the aspects of evaluation and benefits (means being 4.20 and 3.98). 3. The comparison of SCB employees’ participation in the headquarters area regarding CSR classified by demographical factors found the following. Differences in gender, age, educational level, work experience, and position exhibited differences in participation in CSR projects. 4. The relationship between perception of CSR projects and SCB employees’ participation in the headquarters area found that the perception of CSR projects correlated with the participation of SCB employee.